Simultaneous Fractures of Proximal and Distal End of Radius. An Unusual Pattern of Complex Injuries and Clinical Review - G, Kastanis; M., Spyrantis; G., Magarakis; P., Kapsetakis; A., Pantouvaki (International Journal of Innovative Research in Medical Science, 2019)
While the isolated fractures of proximal or distal radius are very common injuries in adults and account to 14% and 18% of all extremity fractures the simultaneous ipsilateral fractures of proximal and distal end of radius are quite uncommon. We present two cases (females 64 and 56 years old) with ipsilateral fractures of radial head and distal end of radius due to a fall. No signs of ligamentous injuries were found in preoperative magnetic resonance imaging’s (MRI). Firstly we treated the distal radius fracture in both cases with volar locking plate, secondly we approached the radial head fracture: in one case (Maison type I) conservatively (plaster of Paris) and in the other case (Maison type III) with radial head replacement. The aim of this study has two objectives: first to increase the awareness of diagnosing this bipolar injury in the emergency department and second to introduce the modalities of treatment.